Factors That Influence Good Governance in The Tanzania Football Federation - Allen Mrindoko; Faisal H Issa (Journal of Business and Management Review, 2023)
Effective management of sports activities entail adherence to some key governance tenets by bodies that oversee sports activities at territorial level. Factors for good governance were investigated in this paper to determine their influence on governance practices in Tanzania Football Federation. A cross-sectional descriptive design was adopted to collect quantitative data from 35 TFF staffs at national office, two region offices (Dar es Salaam and Morogoro) and 4 district offices using a structured questionnaire. The findings show that there is high level of transparency and accountability, financial transparency and control, human resources competence, and policy implementation in daily activities of Tanzania Football Federation. The empirical findings and theoretical thinking of this study contribute to a better understanding of the good governance and its significance on administration and development of sports. the results will also help sports federations or associations, clubs, and other stakeholders in their attempt to develop sports industry.